Manual acupuncture at ST36 attenuates rheumatoid arthritis by inhibiting M1 macrophage polarization and enhancing Treg cell populations in adjuvant-induced arthritic rats. Issue 2 (April 2023) - Yu, Nannan; Yang, Fuming; Zhao, Xue; Guo, Yongming; Xu, Yuan; Pang, Guangchang; Gong, Yinan; Wang, Shenjun; Liu, Yangyang; Fang, Yuxin; Yu, Kun; Yao, Lin; et al.
Objectives: Acupuncture has been found to be effective at relieving many inflammatory pain conditions, including rheumatoid arthritis (RA). We aimed to assess the anti-inflammatory potential of manual acupuncture (MA) treatment of RA using adjuvant-induced arthritic (AIA) rats and to explore the underlying mechanisms. Methods: The anti-inflammatory and analgesic actions of MA at ST36 ( Zusanli ) in AIA rats were assessed using paw withdrawal latency and swelling, histological examination and cytokine detection by enzyme-linked immunoassay (ELISA). The cell–cell communication (CCC) network was analyzed with a multiplex immunoassay of 24 immune factors expressed in the inflamed joints, and the macrophage and Treg populations and associated cytokines regulated by MA were investigated using reverse-transcription quantitative polymerase chain reaction (RT-qPCR), ELISA and flow cytometry. Results: MA markedly decreased heat hyperalgesia and paw swelling in AIA rats. MA-treated rats also exhibited decreased levels of pro-inflammatory cytokines (tumor necrosis factor (TNF)-α, interleukin (IL)-1β) coupled with increased anti-inflammatory cytokines (IL-10, transforming growth factor (TGF)-β1) in the ankle joints at protein and mRNA levels. CCC network analysis confirmed that macrophages are of critical importance and are potential therapeutic targets in RA. Repeated treatment with MA triggered a macrophage phenotypic switch in the paws, with fewer M1 macrophages. Prominent increases in the Treg cell population and TGF-β1 in the popliteal lymph nodes demonstrated the immunomodulatory effects of MA. Furthermore, a selective TGF-β1-receptor inhibitor, SB431542, attenuated the anti-inflammatory effects of MA and MA-induced suppression of the levels of M1-released cytokines. Conclusion: These findings provide novel evidence that the anti-inflammatory and analgesic effects of MA on RA act through phenotypic modulation involving the inhibition of M1 macrophage polarization and an increase in the Treg cell population, highlighting the potential therapeutic advantages of acupuncture in controlling pain and ameliorating inflammatory conditions.